Systemic and Nasal Delivery of Orexin-A (Hypocretin-1) Reduces the Effects of Sleep Deprivation on Cognitive Performance in Nonhuman Primates - Deadwyler, Sam A. (J Neurosci, 2007)
Hypocretin-1 (orexin-A) was administered to sleep-deprived (30–36 h) rhesus monkeys immediately preceding testing on a multi-image delayed match-to-sample (DMS) short-term memory task. The DMS task used multiple delays and stimulus images and effectively measures cognitive defects produced by sleep deprivation (Porrino et al., 2005). Two methods of administration of orexin-A were tested, intravenous injections (2.5–10.0 μg/kg, i.v.) and a novel method developed for nasal delivery via an atomizer spray mist to the nostrils (dose estimated 1.0 μg/kg). Results showed that orexin-A delivered via the intravenous and nasal routes significantly improved performance in sleep-deprived monkeys; however, the nasal delivery method was significantly more effective than the highest dose (10 μg/kg) of intravenous orexin-A tested. The improvement in performance by orexin-A was specific to trials classified as high versus low cognitive load as determined by performance difficulty under normal testing conditions. Except for the maximum intravenous dose (10 μg/kg), neither delivery method affected task performance in alert non-sleep-deprived animals. The improved performance in sleep-deprived animals was accompanied by orexin-A related alterations in local cerebral glucose metabolism (CMRglc) in specific brain regions shown previously to be engaged by the task and impaired by sleep deprivation (Porrino et al., 2005). Consistent with the differential effects on performance, nasal delivered orexin-A produced a more pronounced reversal of sleep deprivation induced changes in brain metabolic activity (CMRglc) than intravenous orexin-A. These findings provide strong evidence for the effectiveness of intranasal orexin-A in alleviating cognitive deficits produced by loss of sleep.